Design and Trial of Electronic Smart Worksheets Based on POE (Predict, Observe, Explain) on Acid-Base Topic - Fatisa, Yuni; Br Galingging, Endang Astuti (JTK (Jurnal Tadris Kimiya), 2021)
This research aims to produce and determine the feasibility of Predict, Observe, Explain (POE) based student electronic smart worksheet. The method used is research and development design. The development stages of this model consist of three stages: defining, designing, and developing. The research respondences were media design experts, learning material experts, chemistry teachers, andÂ tenÂ students. Instruments that used to validate and practical tests are questionnaires. Electronic smart worksheets are created using the articulate storyline application to develop the stages of POE learning. The validity of the worksheet in terms of media, material, practical, and student response results are 80% (valid), 97.14% (very valid), 96.81% (very practical), 89.61% (very practical), respectively. Based on these results, it could be concluded that POE based student electronic smart worksheet is suitable for use as an acid-base learning media.